High Inflammatory Burden: A Potential Cause of Myocardial Injury in Critically Ill Patients With COVID-19 - Song, Yanjun; Gao, Peng; Ran, Tian; Qian, Hao; Guo, Fan; Chang, Long; Wu, Wei; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2020)
Background: Myocardial injury is a severe complication of novel coronavirus disease (COVID-19), and inflammation has been suggested as a potential cause of myocardial injury. However, the correlation of myocardial injury with inflammation in COVID-19 patients has not been revealed so far. Method: This retrospective single-center cohort study enrolled 64 critically ill patients with COVID-19. Patients were categorized into two groups by the presence of myocardial injury on admission. Demographic data, clinical characteristics, laboratory tests, treatments, and outcomes were analyzed in this study. Result: Of these patients, the mean age was 64.8 ± 12.2 years old, and 34 (53.1%) were diagnosed with myocardial injury. Compared with non-myocardial injury patients, myocardial injury patients were older (67.8 ± 10.3 vs. 61.3 ± 13.3 years; P = 0.033), had more cardiovascular (CV) risk factors such as smoking (16 [47.06%] vs. 7 [23.33%]; P = 0.048) and were more likely to develop CV comorbidities (13 [38.2%] vs. 2 [6.7%]; P = 0.003). Scores on the Acute Physiology and Chronic Health Evaluation II (median [interquartile range (IQR)] 19.0 [13.25–25.0] vs. 13.0 [9.25-18.75]; P = 0.005) and Sequential Organ Failure Assessment systems (7.0 [5.0–10.0] vs. 4.5 [3.0–6.0]; P < 0.001) were significantly higher in the myocardial injury group. In addition, patients with myocardial injury had higher mortality than those without myocardial injury (29 [85.29%] vs. 18 [60.00%]; P = 0.022). Cox regression suggested that myocardial injury was an independent risk factor for high mortality during the time from admission to death (hazard ratio [HR], 2.06 [95% confidence interval (CI), 1.10–3.83]; P = 0.023). Plasma levels of high-sensitivity C-reactive protein (hs-CRP), interleukin (IL)-1β, interleukin-2 receptor (IL-2R), IL-6, IL-8, IL-10, and tumor necrosis factor-α (TNF-α) exceeded the normal limits, and levels of hs-CRP, IL-2R, IL-6, IL-8, and TNF-α were statistically higher in the myocardial injury group than in the non-myocardial injury group. Multiple-variate logistic regression showed that plasma levels of hs-CRP (odds ratio [OR] 6.23, [95% CI, 1.93–20.12], P = 0.002), IL-6 (OR 13.63, [95% CI, 3.33–55.71]; P < 0.001) and TNF-α (OR 19.95, [95% CI, 4.93–80.78]; P < 0.001) were positively correlated with the incidence of myocardial injury. Conclusion: Myocardial injury is a common complication that serves as an independent risk factor for a high mortality rate among in-ICU patients with COVID-19. A high inflammatory burden may play a potential role in the occurrence of myocardial injury.